Pemanfaatan Nilai Siri’ Na Pacce sebagai Sarana Mengomunikasikan Identitas Serta Tujuan Sekolah Kristen Di Makassar - Elisa Jhonson Saragih (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
This paper is motivated by anxiety about the challenges faced around the implementation of education in the city of Makassar. In that context Christian schools have major challenges in the social context of Makassar which is experiencing global developments. One of the challenges is how Christian schools are still able to dialogue about identity and purpose by utilizing cultural values ​​or local wisdom. The local wisdom in question is to raise the siri 'na pacce value. Siri 'na pacce is a virtue in the social community of Bugis-Makassar to maintain the integrity and purpose of their lives. The value of the siri’ na pacce is then dialogue with the value of integrity and purpose in biblical teaching that characterizes education in Christian schools. It was found that the value of the siri’ na pacce could be appointed as part of the establishment of the value of integrity to maintain the identity and purpose of education. With the implementation of the siri’ na pacce values, it is expected that Christian schools do not run away in their characteristics and objectives and are not trapped in exclusivity that results in alienation.